Money in the Western legal tradition : Middle Ages to Bretton Woods - Fox, David (David Murray); Ernst, Wolfgang, 1956- (Oxford : Oxford University Press, 2016)
Spanning two great Western legal traditions, the common law of the Anglo-American legal world and the civil law systems of continental Europe, this book analyses monetary law as it has been understood by legal scholars and legal practitioners of the past 800 years.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 8, 2016).
Keywords: Money -- Law and legislation; Law; Laws of specific jurisdictions & specific areas of law